Economic and Cultural Partnership Opportunities between Kupang and Chiba Cities through Sister City Cooperation - Tneh, Vlegon; Maryolanda Zaini (Universitas Muhammadiyah Yogyakarta, 2024)
The Kupang city government has officially proposed a sister city partnership with Chiba, Japan, through representatives of the Japanese government in Bali. This proposal, currently in the initial stages, aims to explore the potential economic and cultural benefits of such a collaboration. This cooperation involves the governments of Kupang City and Chiba City in enhancing economic and cultural cooperation between the two, with the aim of increasing cooperation in trade, investment, and culture, as well as increasing cooperation in education, technology, and infrastructure. This research identifies Chiba as an ideal partner for Kupang, given their various economic and cultural similarities and complementary potentials. By employing qualitative research methods, this study comprehensively examined the prospective advantages of the sister-city relationship. The findings revealed significant opportunities for both cities, including the establishment of an international trade route between Kupang and Chiba and the creation of a central institution dedicated to the research and preservation of their cultures. Based on these insights, the study recommends that the city governments of Kupang and Chiba initiate negotiations and formalize their sister city cooperation, as the anticipated benefits would substantially enhance the development and prosperity of both cities.